Управління фінансово стійким розвитком підприємства на основі сценарного аналізу розподілу фінансових ресурсів - Елецких, С.Я. (Культура народов Причерноморья, 2013)
У статті запропоновано модель управління фінансово стійким розвитком
підприємства, яка дозволяє на основі результатів сценарного аналізу розподілу фінансових
ресурсів підприємства за напрямками інвестування та матеріального стимулювання персоналу, а
також знаходження оптимального співвідношення власного і позикового капіталів підприємства
визначити найбільш ефективну стратегію функціонування підприємства відповідно до критерію
фінансової стійкості. Модель враховує вплив випадкових подій у зовнішньому та внутрішньому
середовищі, що позначається на ефективності його функціонування. В статье предложены подходы к управлению финансово устойчивым развитием
предприятия на основе результатов сценарного анализа распределения финансовых ресурсов по
направлениям инвестирования и материального стимулирования персонала, а также нахождения
оптимального соотношения собственного и заемного капитала, что позволяет определить наиболее
эффективную стратегию функционирования предприятия в соответствии с критерием финансовой
устойчивости. Модель учитывает влияние случайных событий, возникающих во внешней и внутренней
среде предприятия, что отражается на эффективности его функционирования. The article suggests approaches to managing financially sustainable enterprise development based
on the results of scenario analysis of financial resources allocation in the areas of investment, staff incentives, as
well as the optimal ratio of debt and equity capital, which allow determining the most effective strategy for an
enterprise functioning in accordance with the criterion of financial sustainability. The model takes into account
the effect of random events occurring in the external and internal environment of an enterprise, and in its turn
affecting the efficiency of its operation.
This model describes the formation of income from its selling operations and the total costs of the industrial
enterprise. The total costs are formed by direct material costs and a wage bill, which is calculated based on the
number of employees, average wages, and depreciation charges. The dynamics of material resources takes into
account the processes of procurement, warehousing and directly a product write-off considering prices. The
write-off of production volumes is determined according to a production program, which, in turn, is limited to
production capacity and expected demand for the products, but also takes into account finished products in a
stock. The profit adjusted for the value added tax (VAT) and the amount of income tax is a source of an
enterprise owned funds, which, along with obtained at a fixed rate borrowings is a source of financial incentives
for staff, investments to expand production capacity and improve the quality of products.